Impacts of Baobab (Adansonia digitata) Powder on the Poly(Butylene Succinate) Polymer Degradability to Form an Eco-Friendly Filler-Based Composite - Tadda, Musa Abubakar; Gouda, Mostafa; Lin, Xiaochang; Shitu, Abubakar; Abdullahi, Hamza Sulayman; Zhu, Songming; Li, Xiaoli; Liu, Dezhao (Frontiers in Materials, 2021)
Poly(butylene succinate) (PBS) is one of the most common biodegradable plastic polymers that has recently been used in the green environmental field. Enhancement of physicochemical characteristics of these polymers by using plant-based materials like Baobab (Adansonia digitata) will improve its industrial application. This study evaluated Baobab (Adansonia digitata) powder (BP) and PBS composites under various ratios (PBS/BP: 90/10, 80/20, 70/30, 60/40, and 50/50 wt%) for their thermo-mechanical and other physicochemical properties for the industrial application. The nanoscale morphological and elemental characterization were also measured by scanning electron microscope-dispersive X-ray spectroscopy (SEM-EDS). The results revealed that PBS/BP blends of 90/10 and 50/50 showed a significantly reduced melting temperature (Tm) up to 94 °C (p < 0.05) compared to PBS (114 °C). Also, the dynamic viscosity, storage modulus, and loss modulus showed a significant decrease with increasing the ratio of BP in PBS/BP composite, which confirmed faster degradation than the pure PBS. In conclusion, the novel PBS/BP biomaterial is recommended for use as a carbon source for denitrification processes, as an eco-friendly faster degradable natural filler-based polymer. Besides, they could be use in food packaging and biomedical industries.